ADAPTING TO THE TREND OF POPULATION AGING AND AN AGED POPULATION - ELDERLY CARE - Lê Thu Hằng, Phan (Journal of Health and Aging, 2025)
Population aging is a global trend driven by rising life expectancy and declining birth rates, creating profound socio-economic impacts. Vietnam officially entered this stage in 2011 and is now facing one of the world’s fastest aging rates, projected to become an “aged society” by 2036. The country’s primary challenge is the risk of “getting old before getting rich,” as its demographic transition outpaces its national financial accumulation, placing immense pressure on multiple sectors. The healthcare system is unprepared for the surging demand from the elderly, who often suffer from multiple chronic diseases and have treatment costs 7-8 times higher than younger individuals. Vietnam currently lacks sufficient geriatric hospitals, nursing homes, and integrated healthcare models. In terms of social security, a staggering 73% of the elderly do not have a pension and must continue to work or rely on their children, while the pay-as-you-go (PAYG) social insurance system is threatened by demographic shifts. The labor market, despite being in its “golden population” period, is constrained by a low rate of trained labor and low productivity, which affects future financial accumulation capabilities. Simultaneously, traditional family support systems are weakening due to smaller family sizes and geographic dispersion. To adapt effectively, Vietnam needs a comprehensive reform strategy, including promoting sustainable economic growth , improving the labor market , and restructuring the healthcare system towards integrated care, geriatric network development, and long-term care models. Concurrently, developing a multi-pillar social security system is critical to expand coverage and ensure the well-being of the elderly.
Keywords: Population Aging; Elderly Care; Social Security